Administration and management of Saint Louis College archives - Carbajal, Nida N. (City of San Fernando, La Union : [s.n.], 2015)
This study assessed the archival materials of Saint Louis College, San Fernando City, La Union as basis for the establishment of Saint Louis College Archives. Specifically, the study sought to find out the status of archival materials along physical plan and classification in terms of type, year, and value. The study made use of the descriptive survey research design utilizing the qualitative approach. The main sources of the archival materials were the 25 different offices of the Saint Louis College, City of San Fernando, La Union. Inventory of the archival materials was the instrument in gathering the data. Frequency counts and percentages were the statistical tools used to treat the data descriptively. The following are the salient findings of the study: the archival materials were planned to be housed in internet room at the third floor of the College Library Building, a number of the archival materials were school publications preserved from 2004-2013, and of evidential value. Based on the results, the researcher proposed the establishment of Saint Louis College Archives initially to be collected in the internet room at the Third Floor of the College Library Building.
Bibliography: pages 54-56.
CHED-La Union
Keywords: Archives